Global citizenship education in the perspective of strengthening Pancasila student profiles - Sutrisno, Sutrisno; Sunarto, Sunarto; Jumadi, Jumadi (Universitas Negeri Yogyakarta, 2023)
The implementation of Pancasila student profile values in global citizenship education that is applied to national schools abroad must be analyzed to achieve the meaning and goals of global citizenship education. This study aims to provide an overview of the actualization characteristics of the project to strengthen the profile of Pancasila students in global citizenship education. This quantitative research at the Indonesian School of Kuala Lumpur, Malaysia, uses a descriptive method. The research instrument used questionnaire data analysis techniques by collecting, selecting, editing, coding, and presenting data. The results showed that strengthening the profile of Pancasila students was implemented in the form of cultural projects, entrepreneurial projects, archipelago culinary projects, and environmental preservation projects. The implications of this research provide recommendations regarding implementing global citizenship education based on a contextual approach by strengthening the profile of Pancasila students who are oriented towards solving global issues.